PENGARUH RASIO PROFITABILITAS, LIKUIDITAS, SOLVABILITAS, DAN AKTIVITAS TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN ASURANSI YANG TERDAFTAR PADA BURSA EFEK INDONESIA - Habibatul Hidayati; Citra Willyanda Putri (Jurnal Bina Bangsa Ekonomika, 2022)
The purpose of this study is to determine the effect of financial ratios on profit growth in the insurance companies. The variables in this study are Return On Asset (ROA), Cash Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO). Sampling uses a purposive sampling technique with certain criteria. Which produced a sample of 13 insurance companies listed on the Indonesia Stock Exchange in 2016-20120 The analysis in this study uses multiple linear regression analysis by showing the results that Cash Ratio (CR), Debt to Equity Ratio, and Total Asset Turnover (TATO) has no effect on earnings growth, while Return On Asset (ROA) has an effect on earningsgrowth